Analysis of the salivary bacterial microbiome of healthy subjects and patients with oral lichen planus - Dawis, Nurul Hasanah (2025)
The human oral microbiome plays an important role in keeping a balance between beneficial and harmful microorganisms in the oral cavity. Once compromised, the unbalanced microbiota can result in the development of oral diseases. In addition, the oral microbiome among the Malaysian population remains largely uncharacterized, and there is very little information on its composition. It is also not known if changes in the population composition of the oral microbiome is related to the development of Oral Lichen planus (OLP). Thus, the objectives of this research are to characterize and compare the taxonomic of oral microbiome in selected healthy Malaysian and OLP patients. Other than that, to evaluate the ability of bacterial isolates from oral microbiome to produce antibiofilm and antibacterial compounds. Saliva samples were collected from healthy participants and OLP patients, followed by 16S rRNA gene sequencing targeting the V3–V4 region. Sequencing data were processed using QIIME2 and EzBioCloud for OTU clustering and taxonomic assignment. Selected bacterial isolates were further screened for antibiofilm and antibacterial activities. Metagenomic sequencing of the salivary oral microbiomes from 22 healthy subjects revealed that the predominant phyla include Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria and Actinobacteria; while at genus level Streptococcus, Haemophilus, Neisseria, Phorphyromonas and Fusobacterium are the most abundant genera. The oral microbiome from 4 patients with OLP is not different from the healthy subjects, although the proportions of Proteobacteria was higher and Bacteroides is lower. At the genus level, the abundance of potentially pathogenic genera e.g. Neisseria is significantly higher, while Prevotella was less abundant in the OLP samples. A total of 117 bacterial cultures were successfully isolated from the oral samples, and 14 (12.0%) of these isolates produced compounds that inhibit Staphylococcus epidermidis ATCC 35984 biofilm formation with highest activity observed in SA108 (Staphylococcus aureus) at 94.8 ± 22.2%. Furthermore, 12 (10.3%) of the isolates displayed antibacterial ability with highest activity observed in SA112 (uncultured bacterium) against Streptococcus mutans ATCC 25175 at 76.9 ± 54.78%, followed by SA10 (Streptococcus salivarius) against Bacillus subtilis ATCC 6633 at 56.6 ± 3.31%. None of the isolates was able to inhibit the growth of E. coli ATCC 25922 or S. aureus ATCC 25923. Two isolates SA78 (Streptococcus salivarius) and SA10 (Streptococcus salivarius), displayed both antibiofilm and antibacterial activity, suggesting the potential of these oral bacteria as potential probiotics in improving dental health. The abundance of these ‘beneficial’ bacteria were not significantly different in the oral microbiomes of healthy and OLP subjects, indicating that presence of beneficial species is not associated with the propensity to develop OLP. Beneficial bacterial species identified in this study could potentially be developed into oral probiotics or supplements for the improvement of oral health.